Pembagian Harta Bersama dalam Perceraian Ditinjau dari Perspektif Teori Keadilan - Salsabila, Shafa (Universitas Jambi, Fakultas Hukum, 2023)
This thesis examines the Division of Joint Property in Divorce from the Perspective of Justice Theory using 2 court decisions, namely the Banjarmasin Religious Court and the Banten High Religious Court. Based on Law Number 1 of 1974 concerning Marriage, the Compilation of Islam Law, and the Decision of Religious Court Judges. This study aims to determine the legal consequences arising from the judge's consideration in determining the case of division of joint property and analyze the judge's consideration in determining the case of division of joint property based on the theory of justice according to Aristotle and Islamic Law. Formulation of the problem: (1) What are the legal consequences for the judge's consideration in decision Number 1227/Pdt.G/2021/PA. Bjm and decision Number 91/Pdt.G/2021/ PTA.Btn? (2) How is the analysis of the judge's consideration in the division of joint property in decision Number 1227/Pdt.G/2021/PA. Bjm and decision Number 91/Pdt.G/2021/PTA.Btn in the perspective of the theory of justice? This study used normative juridical legal methods. Regarding joint property in marriage, many people ignore it, so there is often an uproar after the judge decides on the divorce between husband and wife. In Article 97 of the Compilation of Islamic Law